Perilaku Pengendalian Bahaya Kecelakaan Kerja di Rumah Tangga Pada Masyarakat Kota Samarinda - Sultan, Muhammad (Keluwih : jurnal kesehatan dan kedokteran, 2021)
The potential hazards and risks in the household are many hazards from physical, chemical, biological and psychological factors. This study aims to explain the hazards of work in households. This study used a descriptive qualitative design with 7 family heads selected as informants. Information collection was carried out in November 2020 in Teluk Lerong Ulu Village, Samarinda City. Interviews and indepth interviews using qualitative interviews and data analysis. The results of the research show that the dangers and risks of work accidents that can cause hospital occupants and eye health problems due to poor lighting, burns, scratches or injuries due to sharp objects, being pinched, crushed and crushed by falling objects. Resident health complaints such as allergic itching and skin diseases, respiratory problems, and complaints of Musculoskeletal Disorder. If not managed properly, these hazards and risks can lead to prolonged health complaints and serious accidents. Therefore, efforts to deal with hazards and risks appropriately are defeated by the daily activities of residents of the household.